The Effectiveness of IT-Based Audiovisual Media in Enhancing Islamic Religious Education Learning Outcomes: A Meta-Analysis - Yahya, Muhamad Slamet; Fian, Khafifatul; Afandi, Rahman; Masruri, Muhammad (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2024)
This study examines the effectiveness of IT-based audiovisual media in improving learning outcomes in Islamic Religious Education (PAI). Using meta-analysis techniques, seven studies were analyzed, each meeting specific criteria such as publication within the past decade and a focus on Islamic education. The data analysis utilized the JASP statistical application, and additional information was collected via questionnaires distributed to 38 educators and 14 students. The results demonstrate that IT-based audiovisual media significantly enhance student learning outcomes, with an average effect size of 0.959, categorized as large. The findings reveal that commonly used media include PowerPoint, digital videos, and educational platforms like Google Classroom. While educators and students show moderate familiarity with IT-based media, their adoption remains inconsistent, with only 52.6% of educators frequently utilizing these tools. This research underscores the importance of integrating IT-based audiovisual media to foster active learning and improve educational quality in Islamic education. It highlights the need for further training and support for educators to maximize the potential of technological innovations in teaching. Future studies are recommended to explore the long-term impact of IT-based media on student engagement and academic performance across diverse educational contexts.